Active tuberculosis patients have high systemic IgG levels and B-cell fingerprinting, characterized by a reduced capacity to produce IFN-γ or IL-10 as a response to M.tb antigens - Flores-Gonzalez, Julio; Urbán-Solano, Alexia; Ramón-Luing, Lucero A.; Cancino-Diaz, Juan Carlos; Contreras-Rodriguez, Araceli; Curiel-Quesada, Everardo; Hernández-Pando, Rogelio; Chavez-Galan, Leslie (Frontiers in Immunology, 2023)
Introduction Tuberculosis (TB) is a bacterial infection caused by Mycobacterium tuberculosis (M.tb). B cells are the central mediator of the humoral response; they are responsible for producing antibodies in addition to mediating other functions. The role of the cellular response during the TB spectrum by B cells is still controversial. Methods In this study, we evaluated the distribution of the circulating B cell subsets in patients with active and latent TB (ATB and LTB, respectively) and how they respond to stimuli of protein or lipid from M.tb. Results Here, we show that ATB patients show an immune fingerprinting. However, patients with drug-sensitive- (DS-TB) or drug-resistant- (DR-TB) TB have altered frequencies of circulating B cells. DS-TB and DR-TB display a unique profile characterized by high systemic levels of IFN-γ, IL-10, IgG, IgG/IgM ratio, and total B cells. Moreover, B cells from DR-TB are less efficient in producing IL-10, and both DS-TB and DR-TB produce less IFN-γ in response to M.tb antigens. Conclusion These results provide new insights into the population dynamics of the cellular immune response by B cells against M.tb and suggest a fingerprinting to characterize the B-cell response on DR-TB.